Neutrophil heterogeneity in complement C1q expression associated with sepsis mortality - Trzeciak, Alissa; Mongre, Raj Kumar; Kim, Ma Rie; Lim, Kihong; Madero, Rafael A.; Parkhurst, Christopher N.; Pietropaoli, Anthony P.; Kim, Minsoo (Frontiers in Immunology, 2022)
Sepsis is a life-threatening systemic inflammatory condition causing approximately 11 million annual deaths worldwide. Although key hyperinflammation-based organ dysfunctions that drive disease pathology have been recognized, our understanding of the factors that predispose patients to septic mortality is limited. Due to the lack of reliable prognostic measures, the development of appropriate clinical management that improves patient survival remains challenging. Here, we discovered that a subpopulation of CD49chigh neutrophils with dramatic upregulation of the complement component 1q (C1q) gene expression arises during severe sepsis. We further found that deceased septic patients failed to maintain C1q protein expression in their neutrophils, whereas septic survivors expressed higher levels of C1q. In mouse sepsis models, blocking C1q with neutralizing antibodies or conditionally knocking out C1q in neutrophils led to a significant increase in septic mortality. Apoptotic neutrophils release C1q to control their own clearance in critically injured organs during sepsis; thus, treatment of septic mice with C1q drastically increased survival. These results suggest that neutrophil C1q is a reliable prognostic biomarker of septic mortality and a potential novel therapeutic target for the treatment of sepsis.